A brief glimpse at a haptic target is sufficient for multisensory integration in reaching movements. (August 2021) - Camponogara, Ivan; Volcic, Robert
Abstract: Goal-directed aiming movements toward visuo-haptic targets (i.e., seen and handheld targets) are generally more precise than those toward visual only or haptic only targets. This multisensory advantage stems from a continuous inflow of haptic and visual target information during the movement planning and execution phases. However, in everyday life, multisensory movements often occur without the support of continuous visual information. Here we investigated whether and to what extent limiting visual information to the initial stage of the action still leads to a multisensory advantage. Participants were asked to reach a handheld target while vision was briefly provided during the movement planning phase (50 ms, 100 ms, 200 ms of vision before movement onset), or during the planning and early execution phases (400 ms of vision), or during the entire movement. Additional conditions were performed in which only haptic target information was provided, or, only vision was provided either briefly (50 ms, 100 ms, 200 ms, 400 ms) or throughout the entire movement. Results showed that 50 ms of vision before movement onset were sufficient to trigger a direction-specific visuo-haptic integration process that increased endpoint precision. We conclude that, when a continuous support of vision is not available, endpoint precision is determined by the less recent, but most reliable multisensory information rather than by the latest unisensory (haptic) inputs.